The Impact of Monetary Policy Instruments on Economic Growth in Türkiye - GAZALOĞLU, MEHMET AHMET (İstanbul Kültür Üniversitesi, 2025)
This study aims to analyze the impact of monetary policy c, including the discount rate, money supply, and required reserve ratio, on Türkiye's economic performance during the period from 2003 to 2024. Advanced econometric models, such as the ARDL model and causality tests, were utilized to examine the short- and long-term effects of these instruments on nominal GDP, real GDP, and inflation rates. The findings reveal that monetary policy instruments significantly influence the economy in the short term, with money supply playing a key role in driving inflation and economic growth. However, these instruments were found to have no statistically significant impact in the long term, indicating the temporary nature of their effects. The study highlights the importance of designing flexible and integrated monetary policies that account for short-term effects while aiming to promote long-term economic sustainability. It offers recommendations for policymakers to achieve economic stability and sustainable growth amid domestic and global challenges.
Keywords: Monetary Policy; Discount Rate; Money Supply; Required Reserve; Inflation; GDP